Legal Protection for Debtors in the Implementation of Fiduciary Guarantee Objects Execution After the Enactment of the Constitutional Court Verdict No. 18/PUU-XVII/2019 - Rayhan Aminuddin Haroen (LEGAL BRIEF, 2022)
This study examines the regulatory arrangements regarding the execution of fiduciary guarantee objects based on the laws and regulations in force in Indonesia, as well as forms of legal protection for debtors in the execution of fiduciary guarantee objects that are not in accordance with Constitutional Court Verdict Number 18/PUU-XVII/2019 using the juridical-normative method, with descriptive research type, and data collected through secondary data consisting of legal materials. The conclusions of this study are: Constitutional Court Verdict Number 18/PUU-XVII/2019 regulates fiduciary guarantee in which there is no agreement on breach of contract (default) and the debtor’s not willing to submit voluntarily the object that is guaranteed for fiduciary guarantee execution, then all legal mechanisms and procedures in implementing the Fiduciary Guarantee must be carried out and implemented in the same way as the execution of court verdict. The issue that arises in the implementation of this regulation is the creditor who often executes the object of a fiduciary guarantee by force without the consent of the debtor, which is contrary to the verdict. Forms of legal protection that can be given to debtors, namely preventive legal protection and repressive legal protection. This study suggests the Financial Services Authority to carry out intensive and strict supervision of creditors and/or execution of debt collectors who violate laws and regulations in the implementation of the object of fiduciary guarantee, as well as enforce law with sanctions, both administrative and criminal if proven to have committed a violation of these provisions.